New Land, New Life: A success story of new land resettlement in Bangladesh - Jenkins, Andrew (CABI, 2020)
The Ganges-Brahmaputra-Meghna deltas has newly emerged 'char' islands, which are very vulnerable, socially, institutionally and environmentally. This book explains how the governments of Bangladesh and the Netherlands cooperated on a land-based rural development project to give settlers security and purpose. The 13 chapters in this book are based on experience gathered from implementing the Char Development and Settlement Project undertaken since 1994.